Assessment of diurnal bird species distribution based on microclimate factors in fragmented forest in Selangor, Malaysia - Mudani, Amin Bakri (2016)
Malaysia is among mega-diversity countries in the world. It. has a lot species of flora and fauna. These flora and fauna species can be found in many type of forest area. Most wildlife in the tropics especially birds' species depends on the forest for cover, food resources and breeding. However, the diversity of bird species arc depends on the environment of the area. Forest fragmentations affect the distribution of bird and can cause the changes, reduction or increasing of bird's species. Sam (2014) indicates that forest fragments may cause changing in microclimate and microenvironment of habitat that may make unsuitable for sensitive birds species. Microclimate and microenvironment factors have a great influenced on the status of bird composition. The relationship of the birds within the fragmented forest areas is difference in terms of microclimate and microenvironment factors (Noss & Cooperrider 1994; Harris 1984). Since forest become under the threats of fragmentation, it may have dire consequence to the diurnal bird's assemblage. Every species of diurnal birds may have different microclimate and microenvironment requirements. Logging and deforestation will disrupt the equilibrium and species richness as it radically alters the microclimate and microenvironment regime of the habitat. Thus, it is important to measure the microclimate and microenvironment features of the bird's habitat as a means of how the disruptions of these parameters affect the distribution of diurnal bird's species in the long run. The study of the assessment of diurnal bird's species distribution based on microclimate and microenvironment factors was conducted in Sungai Chongkak Recreational Forest, Selangor. The objectives of the study are (I) to assess the distribution of diurnal bird's species in Sungai Chongkak Recreational Forest, Selangor. (2) to examine the relationships between diurnal bird's species with microclimate and microenvironment factors at Sungai Chongkak Recreational Forest, Selangor. Transect line and point sampling methodology was used during the study. A multivariate statistic technique of a Canonical Correlation Analysis (CANOCO) was used to examine the relationship between the diurnal bird species with the microclimate and microenvironment factors. The results of the study indicate that there are 41 species of diurnal birds and 524 birds was observed and recorded. It showed that the relationship between diurnal bird's species was highly correlated with the microclimate and microenvironment factors. The correlation was relatively high that scored between 82.4% - 94.5% (see Table 2 and 3). The CANOCO Diagram showed that every diurnal bird's species has their own relationship in microclimate and microenvironment factors (Figure 6 and Figure 7). This study found that the changes of microclimate (such as the increase or decrease of temperature, light intensity and humidity) and microenvironment (such as changes in size of canopy trees, DBH size of trees and number of shrub) influence the distribution of diurnal bird's species. In term of foraging strata, diurnal birds species at study area have their own foraging strata starting from the forest floor to upper canopy. In term of feeding guild, almost all species of diurnal birds observed at study area are insectivore (which is 40 species) except Yellow-breasted Flowerpecker (Prionochilus maculates), 19 species of diurnal birds are frugivore, 11 species of diurnal birds are nectarivore, 7 species of diurnal birds are granivore, 4 species of diurnal birds are carnivore and 2 species of diurnal birds are piscivore. The species of insectivores and frugivores birds are higher in the study area. As conclusion, this research found that microclimate and microenvironment factors may influence the distribution of diurnal bird's species. The changes of microclimate and microenvironment factors also affect the distribution of diurnal bird's species include changes in bird's distribution, bird's assemblage and bird's composition.